Analisis Pengaruh Risk Profile, Good Corporate Governance, Earning, Capital (RGEC) terhadap Profitabilitas pada Bank Umum Syariah yang Terdaftar di Otoritas Jasa Keuangan (OJK) Periode 2018-2022 - Rachma, Jihan Valia; Tristanto, Triyono Adi (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Profit maximization drove the decision to include RGEC in our analysis. This study used a quantitative approach and relied heavily on secondary sources for its data. A significance value of 0.012 <0.05 and a t count value of -2.674 <table -2.037 implies that the NPF variable has a substantial and negative influence on ROA, as shown by the partial analysis. The lack of a meaningful association between GCG and ROA is shown by the fact that neither the t-value (1.801, <2.037) nor the correlation (p = 0.081, p < 0.05) reached the significance threshold. A t count value of 8.949 > of the t table 2.037 and a significant value of 0.000 < of 0.05 show that NOM significantly improves ROA. Also, at the 0.05 level of statistical significance, the t count value of -0.861 and the t table value of -2.037 indicate that the CAR variable is not related to ROA. The RGEC factors have a substantial influence on ROA concurrently, as shown by an Fcount value of 46.657, which is derived from a Ftable value of 2.67, and a significant value of 0.000 <0.05.